G20: Sebuah Mediator untuk Kemajuan Pertumbuhan Ekonomi di Indonesia - Alvela Salsabilah Putri (Jurnal Hubungan Internasional, 2020)
This paper is intended to explain about the global forum that Indonesia associate with—the G20 which is a form of international collaboration in the field of economy and global monetary started since the 1999 as a form of answer towards the monetary crisis that happened in the 1998. G20 was formed to intensify the global economic together hand in hand. Global economic issues seems to have no end and to resolve that the economic world needs an official forum to reach an agreement and solutions to face the global economic challenges. Some national economic issues cannot be resolved alone by the country itself and so the need of teamwork is really crucial to achieve some specific things so the monetary in international level can be resolved. Some developed and developing countries use G20 as the media to review the issue and then review the solution so that they can achieve an ultimate solution that possible throughout the discussion.  Indonesia joined the G20 in 2008 after being deemed to meet the criteria of a strong-based economic country and was the only country in Southeast Asia to become a member of the G20. This journal article was formed using a conceptual method that will describe the systematic G20 forum and its function in helping the world economy and become a container for the improvement of Indonesia’s national economy.